Studi Eksperimental Sekam Padi sebagai Zat Campuran pada Komposit Termoplastik untuk Meningkatkan Sifat Isolator - Yulian Hanif; Agus Riyanto (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
Every year, Indonesia produces a large amount of rice husks. Insulating composites can benefit from the use of rice husks because of their high silica content and low thermal conductivity. The resin composite specimen with fibre and rice husk reinforcing agents is tested for heat insulating properties by insulating the specimen plate. The composite with fibre reinforcement and rice husk ash had the lowest thermal conductivity value of 0.3770 W/m2K, according to the results of the test. To put it another way, ash made from rice husks contains more silica than the husks themselves or the husks that have been milled.